GAMBARAN PEMANJANGAN INTERVAL QTC PADA TERAPI JANGKA PENDEK PASIEN TB MDR - Mansur, Mifta; Suprapti, Budi; Hidayati, Movita; Fatmawati, Umi (JURNAL MEDIA KESEHATAN, 2021)
Problems:Indonesia is one of 30 countries with a high burden of MDR-TB, with an estimated 23,000 (range, 16,000-31,000) cases, with a percentage of 8.8% (range, 6.2-12) for every 100,000 population. One of the challenges in MDR TB treatment is the high rate of side effects. In may 2016, WHO issued a recommendation the use of a standardized 9-11 months short-term therapy regimen. The side effect that can occure in this treatment combination is the prolongation of the QTc interval due to the administration of moxifloxacin (Mfx) and clofazimine (Cfz). The aim of the research: to determine the incidence of QTc interval prolongation in MDR-TB patients receiving short-term therapy regimen. Research method:This research is an observational study with retrospective data collection. Sampling was done by total sampling, obtained 51 subjects entered the exclusion criteria and there were 74 subjects who met the inclusion criteria. The results:there has been QTc interval prolongation with an average 31.31 ± 43.471 ms from the baseline, the longest QTc interval value is 756 ms with a mean of 468,54±33,565 ms, 52 (70,3%) subjects experienced QTc interval prolongation. Conclusions: There was QTc interval prolongation in MDR-TB patients with short-term therapy regimen.